Efficacy of 2-Phenoxyethanol as an Anaesthetic for Adult Redline Torpedo Fish, Sahyadria denisonii (Day 1865) - Thoranam Varkey, Anna Mercy; Sajeevan, Sajan (International Journal of Zoology, 2014)
Efficacy of 2-phenoxyethanol for redline torpedo fish exposed to five concentrations (200, 300, 400, 500, and 600 μlL−1) was evaluated. The time periods necessary for each characteristic stage of induction and recovery were recorded. Results indicated that the induction time of the fish exposed to five anaesthetic concentrations significantly (P<0.05) decreased with increasing concentration but recovery time was independent of concentration. Concentration of 500 μlL−1 (induction time: 173 ± 7 and recovery time: 129 ± 41 seconds) was determined as the minimum effective concentration that induces anaesthesia in less than 3 minutes.